Profiling of phenolic composition in camellia oil and its correlative antioxidant properties analysis - She, Jiarong; Li, Qingyang; Cui, Maokai; Zheng, Qiong; Yang, Jie; Chen, Tiantian; Shen, Danyu; Peng, Shaofeng; Li, Chi; Liu, Yihua (Frontiers in Nutrition, 2024)
Less research has been conducted on the association between camellia oil's (CO) phenolic composition and antioxidant capability. In this study, the phenolic profile of CO and its connection to antioxidant capacity were examined utilizing a combination of widely-targeted phenolic metabolomics and multivariate statistical analysis. A total of 751 phenolics were discovered. The WGCNA was used to link phenols to antioxidants, yielding 161 antioxidant-related phenols from the blue module. In response to several antioxidant assays, 59 (FRAP), 59 (DPPH), and 53 (ABTS) phenolics were identified as differential phenolic markers (DPMs). Further stepwise multiple linear regression revealed 6 DPMs that substantially influenced the antioxidant capacities. Nine metabolic pathways and their associated network mechanisms for the most significant phenolics were developed. This study sheds light on the phenolic content of CO, elucidates their role in antioxidant activity, and lays the groundwork for improving extraction techniques and generating improved product.